Resting ST Amplitude: Prognosis and Normal Values in an Ambulatory Clinical Population. Issue 6 (23rd October 2013) - Zarafshar, Shirin; Wong, Myo; Singh, Nikhil; Aggarwal, Sonya; Adhikarla, Chandana; Froelicher, V.F.
<x xml:space="preserve">Abstract</x> Background There is limited data describing ST segment amplitude in apparently healthy, asymptomatic populations. We analyzed ST amplitude in the standard resting electrocardiogram (ECG) in a large, multiethnic, stable, clinical population. Methods We evaluated computerized ST amplitude measurements from the resting ECGs of 29, 281 ambulatory outpatients collected between 1987 and 1999 at the Palo Alto, VA. With the PR interval as the isoelectric line, both elevation criteria (≥0.1 mV, ≥0.15 mV, and ≥0.2 mV) and depression criteria (≤–0.05 mV or ≤–0.1 mV), were applied. Cox–Hazard survival analysis techniques were used to demonstrate in which leads ST amplitude displacement was associated with cardiovascular (CV) death. To create a cohort without ECG patterns clearly associated with disease, we excluded ECGs with inverted T waves, wide QRS, or diagnostic Q waves and coded the remaining "normal" ECGs for ST elevation and depression to determine a normal range. Results The only ST amplitudes that were significantly and independently associated with time to CV death when adjusted for age, gender, and ethnicity were ST depression in all of the lateral leads (I, V4–V6). When isolated to the inferior leads, (II and AVF), no ST amplitude criteria were associated with CV death. Among the "normal ECG" subgroup the precordial leads exhibited the greatest median ST amplitudes and the most significant differences between the leads, genders and ethnicities. Conclusions Significant differences in ST amplitude were present in the precordial leads according to gender and ethnicity. This was particularly apparent when amplitude threshold were set for comparisons. Our findings provide the normal range for ST amplitude that when exceeded, should raise clinical concern.